Sensorless Vector Control of AC Induction Motor Using Sliding-Mode Observer - Phuc Thinh Doan; Tan Tien Nguyen; Sang Kwun Jeong; Sea June Oh; Sang Bong Kim (International Journal of Science and Engineering, 2013)
This paper develops a sensorless vector controlled method for AC induction motor using sliding-mode observer. For developing the control algorithm, modeling of AC induction motor is presented. After that, a sliding mode observer is proposed to estimate the motor speed, the rotor flux, the angular position of the rotor flux and the motor torque from monitored stator voltages and currents. The use of the nonlinear sliding mode observer provides very good performance for both low and high speed motor operation. Furthermore, the proposed system is robust in motor losses and load variations. The convergence of the proposed observer is obtained using the Lyapunov theory. Hardware and software for simulation and experiment of the AC induction motor drive are introduced. The hardware consists of a 1.5kw AC induction motor connected in series with a torque sensor and a powder brake. A controller is developed based on DSP TMS320F28355. The simulation and experimental results illustrate that fast torque and speed response with small torque ripples can be achieved. The proposed control scheme is suitable to the application fields that require high performance of torque response such as electric vehicles. doi:http://dx.doi.org/10.12777/ijse.4.2.2013.39-43 [How to cite this article: Doan, P. T., Nguyen, T. T., Jeong, S. K., Oh, S. J., & Kim, S. B. (2013). Sensorless Vector Control of AC Induction Motor Using Sliding-Mode Observer. INTERNATIONAL JOURNAL OF SCIENCE AND ENGINEERING, 4(2), 39-43; doi: http://dx.doi.org/10.12777/ijse.4.2.2013.39-43]